BERAT LAHIR SEBAGAI FAKTOR DOMINAN TERJADINYA STUNTING PADA BALITA (12â59 BULAN) DI SUMATERA (ANALISIS DATA RISKESDAS 2010) - -, Fitri (Sistem Informasi, 2013)
Stunting is very short state of body so that the deficit exceeded -2 SD below the median length or height. Stunting is a public health issue because it deals with an increased risk of morbidity and mortality, delayed motor development, and mental growth retardation. The general objective of research is to know the dominant factor related with stunting in infants (12-59 months) in Sumatra in 2010. This study uses cross sectional research design and quantitative method with 3126 toddlers sample. Processing and analyzing data using chi square test (bivariate) and multiple logistic regression (multivariate). The analysis showed that based on the index TB/U, stunting toddlers as much as 37.5% and 62.5% of normal. The results of chi square test showed significant relationship between stunting with birth weight, energy intake, protein intake, sex, maternal education, area of residence and economic status of families. The results of multivariate analysis showed the birth weight variable is the most dominant factor associated with stunting after being controlled with sex, area of residence and economic status of families variables.